Red lentil (Lens culinaris) extract as a novel natural coagulant for turbidity reduction: An evaluation, characterization and performance optimization study - Chua S.-C.; Malek M.A.; Chong F.-K.; Sujarwo W.; Ho Y.-C. (MDPI AG, 2023)
Coagulation; Extraction; Field emission microscopes; Fourier transform infrared spectroscopy; Inorganic chemicals; Physicochemical properties; Polysaccharides; Reclamation; Scanning electron microscopy; Surface properties; Turbidity; Wastewater treatment; Field emission scanning electron microscopy; Lentil extracts; Natural coagulant; Performance optimizations; Physicochemical characteristics; Response surface methodology; Settling characteristics; Water and wastewater treatments; Chemical water treatment; chemical substance; coagulation; flocculation; legume; optimization; performance assessment; plant extract; polysaccharide; response surface methodology; turbidity; wastewater treatment; water treatment; Lens culinaris